Mesenchymal stem cells enchanced by salidroside to inhibit ferroptosis and improve premature ovarian insufficiency via Keap1/Nrf2/GPX4 signaling - Lixuan Chen; Yingnan Wu; Tiying Lv; Rui Tuo; Yang Xiao (Redox Report)
Background Regenerative medicine researches have shown that mesenchymal stem cells (MSCs) may be an effective treatment method for premature ovarian insufficiency (POI). However, the efficacy of MSCs is still limited.Purpose This study aims to explain whether salidroside and MSCs combination is a therapeutic strategy to POI and to explore salidroside-enhanced MSCs inhibiting ferroptosis via Keap1/Nrf2/GPX4 signaling.Methods The effect of salidroside and MSCs on ovarian granular cells (GCs) was analyzed. After treatment, hormone levels and -fertility of rats were measured. Lipid peroxidation levels, iron deposition and mitochondrial morphology were detected. The genes and proteins of Keap1/Nrf2/GPX4 signaling were examined.Results Salidroside and MSCs were found to inhibit cell death of GCs by reducing peroxidation and intracellular ferrous. Salidroside promotes the proliferation of MSCs and supports cell survival in ovary. Salidroside combined with MSCs therapy restored ovarian function, which was better than MSCs monotherapy. Salidroside-enhanced MSCs to inhibit ferroptosis. The results showed activation of the Keap1/Nrf2/GPX4 signaling and an increase in anti-ferroptosis molecule.Conclusions Salidroside-enhanced MSCs as a ferroptosis inhibitor and provide new therapeutic strategies for POI. The possible mechanisms of MSCs were related to maintaining redox homeostasis via a Keap1/Nrf2/GPX4 signaling.